Preterm birth, progress and challenges. Prologue - Pacheco-Romero, José (2018)
This article is an introduction to the symposium Perinatal approach to preterm labor that includes themes on causality, management of the mother, advances in the management of the premature newborn, and the future of mother and baby. This prologue includes figures that show how the incidence of prematurity has increased over time. Nevertheless, advances in perinatology and neonatology allow more and better survival for infants born preterm and with very low weight. Preventive measures in the mother at risk also contribute to better perinatal results.